The Mourning Period (Iḥdād) for Widowers: A Gender and Sociological Perspectives - Nur Fadhilah; Nihayah Nihayah; Ahmad Muhtadi Anshor; Hamadah Ashfiya (Sawwa: Jurnal Studi Gender, 2025)
Despite extensive scholarship on female mourning practices (iḥdād), male mourning within Islamic legal and gender studies is largely overlooked, creating a significant gap in understanding how widowers manage grief culturally and religiously. This study focuses on the neglected male mourning practices in Islamic contexts and how widowers navigate their grief. Through a qualitative method involving in-depth interviews with five widowers, alongside observations and document analysis (in the form of local prayer books, memorial schedules, and religious guidance texts), the data was thematically analyzed using the Braun and Clarke framework, combined with phenomenological insights to uncover emotional and ethical patterns. The findings indicate that widowers engage in ethical negotiations—such as postponing remarriage and avoiding social gatherings—that reflect an interplay between Islamic teachings and Javanese cultural norms. This research suggests that the Qira'ah Mubādalah perspective offers a valuable interpretive framework that situates these mourning practices within a context of reciprocal ethics rooted in spirituality, which has broader implications for gender ethics in contemporary Islamic discourse.